Al-Iklīl Fī Istinbāṭ Al-Tanzīl: an Analysis of Al-Suyūṭī’s Interpretation Of Criminal Verses - Al Zhafir, Turkey (Jurnal Moderasi, 2024)
This study explores Al-Iklil fi Istinbat al-Tanzil by Jalaluddin al-Suyuti, focusing on his interpretation of criminal verses in the Qur'an. Using a qualitative method based on literature review with content analysis, this study identifies al-Suyuti's textual-normative approach in deriving legal provisions (istinbat) from verses on adultery, theft, false accusations, murder, and armed robbery. His concise interpretation reflects classical Islamic legal principles such as justice, crime prevention, and social protection, but lacks social-historical context. This study argues that although Al-Iklil provides a fundamental normative framework, its application in modern Islamic criminal law requires contextual reinterpretation in line with contemporary legal systems and human rights standards. This work remains relevant as a legal-ethical reference in the corpus of Islamic jurisprudence.